Optimalisasi Motivasi dan Hasil Belajar Peserta Didik Mata Pelajaran Ekonomi KD 3.6/4.6 Materi Bank Sentral, Sistem Pembayaran dan Alat Pembayaran dalam Perekonomian Indonesia Melalui Model Projects Based Learning Metode Pemberian Tugas di Kelas X.IPS.3 M - Rasna Wirda (Departement of Mathematics Education, 2022)
This study aims to see and analyze the increase in motivation and learning outcomes of students in economic subjects with the material Central Bank, Payment Systems and Payment Instruments in the Indonesian Economy with the Projects Based Learning Model Giving Assignment Method in Class X.IPS.3 MAN 2 Payakumbuh Even Semester 2021/2022 Academic Years. This research consists of two cycles, where each cycle consists of; planning, action, reflection, and evaluation. It was carried out from January to April 2022. The data was processed in each cycle and then analyzed using percentages. The results obtained from this study are the Project based learning model, the assignment method can increase students' motivation and learning outcomes. This is evidenced by an increase in student motivation in cycle I and cycle II, the results obtained for motivation are 80.75% while in cycle II it is 92.85%. The increase in the average value of learning outcomes for knowledge competence in Cycle I was from 80.56 to 90.00 in Cycle II and learning outcomes for skill competencies increased from 86.39 in Cycle I to 91.53 in Cycle II. Students' learning mastery for knowledge in the first cycle which was completed was 30 people (83.33%) and for skills 30 people were also completed (83.33%) while in the second cycle the results were obtained for knowledge of 34 people who were complete (94.44%) while for the skills of 35 people who have completed (97.22 %). The conclusion obtained from this research is that the use of the Project based learning model of the assignment method can increase students' motivation and learning outcomes.